The Role Of Coaching Health Center Leaders In Improving Indicator Achievements Minimum Service Standards At Kuok Community Health Center : Literature Review - Jayandra, Jayandra (Lembaga Penelitian Dan Publikasi Ilmiah (LPPI) Yayasan Almahmudi Bin Dahlan, 2025)
This article discusses the important role of leadership development in improving the achievement of minimum service standard indicators at Kuok Health Center. Health is a basic need for every human being. Minimum Service Standards are provisions regarding the type and quality of minimum basic services which are mandatory government affairs that every citizen has the right to receive. This study uses a systematic method by reviewing literature related to the development of Puskesmas leaders with program managers at Kuok Health Center. Scientific articles, books, and other documents relevant to the research topic have been collected and analyzed to identify significant trends and findings in the context of coaching communication at Kuok Health Center. The conclusion is that the coaching program by the Puskesmas leader to the team is a useful development method. Coaching will be successful if a good process is built between the coach and the coachee. Therefore, the coaching process requires a strategy from the coach and the role of the organization is considered important in developing coaching from the leader to the staff. The benefits that can be seen from the implementation of the coaching program are increased motivation and job satisfaction. In addition, this can provide team spirit and work engagement and can help others build their self-confidence.